Complexity of the pediatric trauma care process: Implications for multi-level awareness - Wooldridge, Abigail (Cogn Technol Work, 2018)
Trauma is the leading cause of disability and death in children and young adults in the US. While much is known about the medical aspects of inpatient pediatric trauma care, not much is known about the processes and roles involved in in-hospital care. Using human factors engineering (HFE) methods, we combine interview, archival document and trauma registry data to describe how intra-hospital care transitions affect process and team complexity. Specifically, we identify the 53 roles directly involved in patient care in each hospital unit and describe the 3324 total transitions between hospital units and the 69 unique pathways, from arrival to discharge, experienced by pediatric trauma patients. We continue the argument to shift from eliminating complexity to coping with it and propose supporting three levels of awareness to enhance the resilience and adaptation necessary for patient safety in health care, i.e. safety in complex systems. We discuss three levels of awareness (individual, team and organizational) and describe challenges and potential sociotechnical solutions for each. For example, one challenge to individual awareness is high time pressure. A potential solution is clinical decision support of information perception, integration and decision making. A challenge to team awareness is inadequate “non-technical” skills, e.g., leadership, communication, role clarity; simulation or another form of training could improve these. The complex, distributed nature of this process is a challenge to organizational awareness; a potential solution is to develop awareness of the process and the roles and interdependencies within it, by using process modeling or simulation.